PERAN BADAN PENGAWAS PEMILIHAN UMUM DALAM MELAKUKAN PENCEGAHAN PELANGGARAN DI PEMILIHAN KEPALA DAERAH KOTA PEKANBARU TAHUN 2024 - Fathi’ah, Syalaisa Amani; Nasution, Hazqon Fuadisu (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Regional Head Elections (Pilkada) are a concrete manifestation of democracy in Indonesia, but their implementation remains vulnerable to violations such as money politics, administrative violations, and the lack of impartiality of state civil servants. This study aims to analyze the role of the Pekanbaru City Election Supervisory Agency (Bawaslu) in preventing violations in the 2024 Pilkada. The approach used was descriptive qualitative through interviews, documentation, and literature review, utilizing Talizuduhu Ndraha's role theory, which divides roles into normative and effective indicators. The results show that normatively, Bawaslu has implemented its preventive function through outreach, education, and participatory oversight. However, effective oversight is still hampered by limited resources, weak reporting evidence, and low public participation. These conditions have resulted in suboptimal efforts to prevent violations that threaten the integrity of the Pilkada. This study emphasizes the need for increased institutional capacity and community collaboration to strengthen the oversight function so that local democracy in Pekanbaru can be realized transparently and with integrity. Keywords: Bawaslu, Pilkada, Violation Prevention, Role, Election Oversight